COVID-19-Related anxiety in nurses working on front lines in Turkey - Murat Saricam (Kashan University of Medical Sciences, 2020)
Background: The novel coronavirus (COVID-19) pandemic constituted serious impacts globally. Objectives: The aim of this study was to investigate the pandemic related anxiety in nurses working in a university hospital in Turkey. Methods: A questionnaire-based study was conducted to include 123 nurses working in the wards and intensive care units (ICUs). Data concerning age, gender, marital status, having a child, duration of employment, workplace, and state anxiety score were collected for every participant. Turkish version of Spielberg's State-Trait Anxiety Inventory (Form TX-1) was applied to calculate the anxiety scores. Independent samples t- test and Chi-squared test were used for the statistical analysis. Results: Fifty-seven (46.3%) nurses demonstrated an elevated level of anxiety. COVID-19-related anxiety was closely associated with advancing age and years of experience, having a child and working in the wards rather than ICUs (P < 0.05). However, gender and marital status did not affect significantly on the development of higher anxiety (P > 0.05). Conclusions: Alleviation of worries of health-care providers is crucial in addition to the prevention of self-contamination to provide the continuation of medical services.